2018
DOI: 10.1007/s00345-018-2398-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the effects of deep and moderate neuromuscular blockade during transurethral resection of bladder tumor on endoscopic surgical condition and recovery profile: a prospective, randomized, and controlled trial

Abstract: Deep NMB and reversal with sugammadex improved the endoscopic surgical condition without complications compared with moderate NMB and reversal with sugammadex in patients undergoing TURB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…The deep NMB group showed no significant difference in recovery profiles in our study; postoperative pulmonary complications, including desaturation, respiratory depression, and atelectasis, were comparable between the two groups, which may be explained by sugammadex administration to both groups. This is in agreement with a previous study that compared results between deep and moderate NMB, in patients undergoing transurethral resection of the bladder [18], and found that no postoperative pulmonary complications occurred in either cases.…”
Section: Discussionsupporting
confidence: 93%
“…The deep NMB group showed no significant difference in recovery profiles in our study; postoperative pulmonary complications, including desaturation, respiratory depression, and atelectasis, were comparable between the two groups, which may be explained by sugammadex administration to both groups. This is in agreement with a previous study that compared results between deep and moderate NMB, in patients undergoing transurethral resection of the bladder [18], and found that no postoperative pulmonary complications occurred in either cases.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a number of studies showed reduced muscle injury after deep neuromuscular blockade during total hip replacement and the levels of IL-6, CPK, and LDH were lower after the operation [ 23 , 24 ]. Deep neuromuscular blockade can help to reduce muscle injury and reduce the stress of an operation and perioperative inflammation to a certain extent through improving surgical space conditions and making the operation easier to perform for the surgeon [ 25 27 ]. However, deep neuromuscular blockade is not that easy to popularize because of the prolonged recovery time and increased incidence of residual neuromuscular blockade after the operation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Deep neuromuscular blockade can help to reduce muscle injury and reduce the stress of an operation and perioperative in ammation to a certain extent through improving surgical space conditions and making the operation easier to perform for the surgeon. [25][26][27] But it is not so easy to popularize deep neuromuscular blockade because of the prolonged recovery time and increased incidence of residual neuromuscular blockade after the operation. [11] Another possible reason can be that Sugammadex, the rocuronium speci c antagonist, is quite expensive in China and out of the medical insurance list.…”
Section: Discussionmentioning
confidence: 99%